Manejo de Mercancías Químicas peligrosas en puerto Caldera, Puntarenas, Costa Rica. - Mora, José Carlos (2009)
Puerto Caldera, located in Puntarenas, Costa Rica, is one of the most important Harbors of Central America, which is a key point to transport about 1.5 millions of metric tons of different categories of products every year, including dangerous chemical merchandise. The chemical has have originated emergencies, which has given rise to the necessity to asses load and unload process, and storage. In attention to the matter the most important aspects related to the fulfillment of the national and international norms during the merchandise dangerous transportation in Harbors were evaluated. According to the evaluation of the different handling, storage and transportation processes, Puerto Caldera, face among others the following problems: Personal training necessities addressed to the employees involved in the process of handling dangerous merchandise. Insufficient equipment and materials to guarantee a safe environment. The permanence of merchandise for long periods in warehouse. Unsuitable conditions of warehouse for the proper storage of chemical merchandise. Absence of classification and location criteria of dangerous chemical merchandise in the unloading and loading areas as well as in warehouse. Based up the previous evaluations, the following aspects were developed: An improvement plan for adequate handling of chemical merchandise. Recommendation of specific guidelines to create a Contingencies Plan. The purposes of the two aspects are to promote actions to diminish the risk of accidents associated to the handling of a dangerous merchandise. In the same way, it was proposed a Plan of Improvement and basic lineaments to elaborate a Plan of Contingencies that includes actions to diminish the risk of accidents associated to the handling of dangerous merchandise and to diminish the consequences, in case of accident, as far as the loss of lives, damages to the people, the property and the environment. All this will make Puerto Caldera a safe place for the handling of chemical dangerous merchandise.